Risk Factor for Musculoskeletal Disorder in Construction Worker: Literature Review - Arif Rahmat Abdullah; Indri Hapsari Susilowati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Musculoskeletal Disorders (MSDS) is a condition involving degenerative health problems or inflammation that occurs in workers, affecting joints, ligaments, muscles, tendons and blood vessels. Sufferers of muscle and skeletal disorders as an occupational disease are the largest number of cases of occupational disease in Europe compared to other diseases in 2017. Objective: This research aims to identify factors Risk factors for muscle and skeletal disorders in construction workers. Method: This research uses the method literature study using the PRISMA approach (preferred reporting items for systematic reviews and meta-analyses). When searching for journals that are relevant to the research topic, use a search engine Science Direct and ResearchGate using the keyword